PERAN GEN Z DALAM MENGUATKAN DEMOKRASI DAN KEWARGAAN AKTIF - Jihan Rafeyfa Syafitri; Tengku Camelia Handriansyahri; Raifa Meiliza Dwi Harianti; Geby Trisnawati Br. Manalu; Selvia Imelda Sitohang; Najwa Chantika; Ria Manurung; Silvia Annisa (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
As an age group born and raised in the digital era, Gen Z holds a strategic opportunity to help strengthen democracy in Indonesia. Gen Z are digital natives who not only rely on formal political participation through elections but are also actively involved in non-formal spaces such as communities, social media, and advocacy movements. The purpose of this study is to explain the role of Gen Z in strengthening democracy and active citizenship by employing Karl Mannheim’s generational theory and Carole Pateman’s participatory democracy theory. The literature review method was applied in this study by examining journals relevant to the research topic. The literature used includes national and international journal articles published between 2015–2025, focusing on participatory democracy, active citizenship, political participation among Gen Z, and digital literacy. The discussion results show that Gen Z are more politically aware and engaged in society through public involvement, thereby fostering an inclusive, transparent, and participatory democracy. Although they face several challenges, including political apathy, elite domination, and digital disinformation, Gen Z still plays a vital role in improving the governance of Indonesian democracy. The conclusion of this study emphasizes that Gen Z actively participates in both national and global life and serves as a crucial foundation for the sustainability of democracy.